The role of exercise and physical activity on aging-related diseases and geriatric syndromes - Kushkestani, Mehdi; Parvani, Mohsen; Ghafari, Mahmood; Avazpoor, Zahra (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
Aging is a complex process of physiological and social changes that leads to various diseases. The number of elderly people in the world is increasing dramatically and it should be noted that rapid population aging represents a major public health burden. On the other hand, providing an appropriate and low-cost approach to control and prevent complications such as chronic diseases, physical dysfunction, and the geriatric syndrome is necessary. Also, numerous studies have shown that participation in physical activity and exercise training reduces the incidence of dysfunctional capacity, cardiovascular and metabolic disease, as well as the premature death rate in older adults. After plenty of precise observations about the role of exercise on aging-related diseases and geriatric syndromes articles, the benefits of exercise and physical activity in older adults will be more tangible. Therefore, the first purpose of the present review was to investigate the mechanisms of PA and exercises that are involved in the prevention of aging-related diseases and GS using current evidence (from 2015 onwards). Also, the purpose of this study was to provide an exercise guideline (aerobic and resistance training) based on recent evidence (from 2015 onwards).